A trivalent vaccine consisting of "flagellin A+B and pilin" protects against Pseudomonas aeruginosa infection in a murine burn model. (January 2020) - Hashemi, Farhad B.; Behrouz, Bahador; Irajian, Gholamreza; Laghaei, Parisa; Korpi, Fatemeh; Fatemi, Mohammad Javad
Abstract: Pseudomonas aeruginosa is a common nosocomial pathogen in burn patients, and rapidly achieves antibiotic resistance, and thus, developing an effective vaccine is critically important for combating P. aeruginosa infection. Flagella and pili play important roles in colonization of P. aeruginosa at the burn wound site and its subsequent dissemination to deeper tissue and organs. In the present study, we evaluated protective efficacy of a trivalent vaccine containing flagellins A and B (FlaA + FlaB) + pilin (PilA) in a murine burn model of infection. "FlaA + FlaB + PilA" induced greater protection in P. aeruginosa murine burn model than the single components alone, and it showed broad immune protection against P. aeruginosa strains. Immunization with "FlaA + FlaB + PilA" induced strong opsonophagocytic antibodies and resulted in reduced bacterial loads, systemic IL-12/IL-10 cytokine expression, and increased survival after challenge with three times lethal dose fifty (LD50) of P. eruginosa strains . Moreover, the protective efficacy of "FlaA + FlaB + PilA" vaccination was largely attributed to specific antibodies. Taken together, these data further confirm that the protective effects of "FlaA + FlaB + PilA" vaccine significantly enhance efficacy compared with antibodies against either mono or divalent antigen, and that the former broadens the coverage against P. eruginosa strains that express two of the three antigens. Highlights: The first trivalent vaccine against P. aeruginosa infection that provides full protection. Complete survival of FlaA + FlaB + PilA vaccinated mice infected by heterologous strains of P. aeruginosa. FlaA + FlaB + PilA induces superior opsono-phagocytic activity as compared to mono- or divalent vaccines. Synergistic immune response to FlaA + FlaB + PilA components; with no cross-reactive interference.